2011
DOI: 10.2147/ijwh.s16702
|View full text |Cite
|
Sign up to set email alerts
|

Understanding hypertriglyceridemia in women: clinical impact and management with prescription omega-3-acid ethyl esters

Abstract: Background:Elevated triglycerides (TGs) are a common lipid disorder in the US and are associated with comorbidities such as pancreatitis, obesity, type 2 diabetes, and metabolic syndrome. TGs are generally elevated in postmenopausal women compared with premenopausal women. Meta-analysis has shown that elevated TGs are associated with an increased risk of coronary heart disease (CHD).Objective:This article provides a general overview of TG metabolism and reviews data on the epidemiology and risk of elevated TGs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 67 publications
0
11
0
2
Order By: Relevance
“…Natural menopause is known to be associated with increased central adiposity [24]; further, in cases of similar mean BMI values for premenopausal and postmenopausal women, increased WC has been found to be significantly associated with postmenopausal status after adjusting for age [20]. A previous study reported that serum 25(OH)D levels were negatively associated with WC [34].…”
Section: Discussionmentioning
confidence: 92%
“…Natural menopause is known to be associated with increased central adiposity [24]; further, in cases of similar mean BMI values for premenopausal and postmenopausal women, increased WC has been found to be significantly associated with postmenopausal status after adjusting for age [20]. A previous study reported that serum 25(OH)D levels were negatively associated with WC [34].…”
Section: Discussionmentioning
confidence: 92%
“…While the benefits of fish oil in the diet are widely known and appreciated, including lowered coronary arteriosclerosis risk, a product (Lovaza®) has recently appeared on the market with the specific therapeutic goal of reducing serum triglycerides (Dayspring, 2011). This product is composed of the ethyl esters of various ω-3 fatty acids obtained from fish, mainly comprised of EPA (20:5n3) and DHA (22:6n3), administered as 400 mg/day.…”
Section: Some Marine Drug Discovery Success Storiesmentioning
confidence: 99%
“…The reason for this gender difference might be related to the mechanism of hypertriglyceridemia in postmenopausal women, which induced small LDL particles. [18][19][20] There were age or gender-related differences in the ability to generate sdLDL-C from LDL-C. This ability in men was higher than that in women for all age groups or standardized groups, which is identical to the fact that atherosclerosis is more common in men than in women, considering sdLDL-C is a highly atherogenic factor.…”
Section: Discussionmentioning
confidence: 90%